2015
DOI: 10.1002/pmic.201500023
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of protein N‐termini by charge reversal of internal peptides

Abstract: Protein N-termini provide useful information for the understanding of posttranslational processing of proteins. The majority of proteins undergo N-terminal processing, such as proteolytic truncation or modifications like acetylation. Multiple methods currently exist for the enrichment of N-terminal peptides for proteomic analyses. Here, we report a novel, simple, and straightforward N-terminomic strategy, based on charge reversal of internal peptides followed by their removal through strong cation exchange chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…3B), thus signaling aberrant cleavage within the protein chain. In another recent degradomic study of mouse embryonic kidney, we also observed a reduced level of dimethylated peptides when compared with acetylated peptides (18). By introducing a novel gel-based enrichment of N termini, we observed a significantly reduced fraction of peptides mapping to internal positions (18).…”
Section: Enrichment Of N-terminal Peptides From Ffpe Specimens-mentioning
confidence: 74%
See 3 more Smart Citations
“…3B), thus signaling aberrant cleavage within the protein chain. In another recent degradomic study of mouse embryonic kidney, we also observed a reduced level of dimethylated peptides when compared with acetylated peptides (18). By introducing a novel gel-based enrichment of N termini, we observed a significantly reduced fraction of peptides mapping to internal positions (18).…”
Section: Enrichment Of N-terminal Peptides From Ffpe Specimens-mentioning
confidence: 74%
“…In another recent degradomic study of mouse embryonic kidney, we also observed a reduced level of dimethylated peptides when compared with acetylated peptides (18). By introducing a novel gel-based enrichment of N termini, we observed a significantly reduced fraction of peptides mapping to internal positions (18). For this reason, we consider it likely that the increased proportion of dimethylated N termini in cryopreserved samples is indicative of increased proteolysis during cryopreservation rather than signifying limited reactivity of N termini from FFPE samples.…”
Section: Enrichment Of N-terminal Peptides From Ffpe Specimens-mentioning
confidence: 82%
See 2 more Smart Citations
“…B). Modifications of proteins and polypeptides play an important role in the regulation of cellular and biological function, and the modification and electric charge influence electric migration rate of the protein (Lai et al ., ). Then, we suggested that this difference of the molecular weight of cofilin in Triton‐soluble and Triton‐insoluble protein fractions was from the modification and electric charge.…”
Section: Discussionmentioning
confidence: 97%